Plasmapheresis and Plasma Donation: Challenges in the Blood/Plasma Supply Chain. (July 2022) - Rivera, José; Lozano, Miquel
Voluntary non-remunerated blood donation is well-established in many countries; however, this approach is under pressure to provide sufficient plasma for future needs. In this article we consider various aspects of plasma donation, including donor characteristics, health and safety issues, and motivating factors, including the potential role of incentives. The status of plasma donation in various European countries, and challenges associated with the COVID-19 pandemic are also discussed. Common motivators for plasma donors include the benefit that donated plasma provides for other people, the sense that helping others is in their nature, a sense of pride at undertaking a special task, and the desire to achieve donation goals. Motivations may differ between age groups and gender. Donating plasma is safe and adverse events are infrequent, with the most common being hypotensive/vasovagal events and phlebotomy events. The main reasons plasma donors discontinue are socioeconomic, relating to the time required and conflicts with work and other commitments. When persuading donors to convert from whole blood to plasma donation, face-to-face requests are more successful than leaflets or telephone/email requests, and clear information addressing health and safety concerns is needed. However, telephone/email communication can be helpful for encouraging plasma donors to return for future donations or to donate more frequently. There is ongoing debate about non-remunerated versus remunerated plasma donation. Remuneration may be an incentive for some individuals, whereas it may deter people who have a strong altruistic drive. It has been suggested that a combination of paid and unpaid donation systems could cover a wider range of potential donors. Most European countries currently have non-remunerated donor systems, but a few do allow monetary compensation.